Managing reality. Book one, - Mitchell, Bronwyn; Trebes, Barry (ICE Publishing, 2018)
This work focuses on the fundamental cultural changes and mind shift that is required to successfully manage the practicalities of the ECC in use. It will be useful reading for those considering using the ECC but need further information, or those who are already using the ECC but need further insight into its rationale.
Includes index.
Keywords: Civil engineering contracts -- Great Britain.; Construction contracts -- Great Britain.; elektronické knihy; electronic books